The Prince, the KAR.KID Women and the arzana-house: A Hittite Royal festival to the goddess Kataḫḫa (CTH 633) - Taggar-Cohen, Ada (2010)
CTH 633 is a Hittite text including a prescribed ritual of a festival to be performed by a prince. Its first publisher read the text as a rite of passage, initiating a young prince into adulthood, based on assumptions of the meaning of three key terms in the text: the verbal noun ḫaššumaš which is the name of the festival, the location where the rite takes place, which is the arzana- house, and the participation of KAR.KID women, recognized in Mesopotamian scholarship as “prostitutes”. This article offers an alternative understanding of this text based on reexamination of these terms. While setting the ritual in the context of Hittite royal state religion, the ritual is interpreted from a methodological point of view as a political rite , part of the religious activities aimed at conferring royal legitimacy on the prince, who is the next in line to become the Great King of Ḫatti. The role of the KAR.KID women in the cultic activity is explained, and the arzana- house is identified as a place of cult.
Keywords: Political Rite; KAR.KID Women; arzana-house; ḫaššumaš; Prince